Effects of Chronic Alcohol Use Disorder on the Visual Tilt Illusion - Gao, Guoqing; Yin, Liangshuang; Cheng, Jun; Tao, Rui; Liu, Yu; Pang, Liangjun; Wang, Zhengchun (Frontiers in Psychiatry, 2021)
Rationale Among the serious consequences of Alcohol Use Disorder (AUD) is the reduced ability to process visual information. It is also generally agreed that AUD tend to occur with disturbed excitation-inhibition (EI) balance in the central nervous system. Thus, a specific visual behavioral probe could directly qualify the EI dysfunction in patients with AUD. The tilt illusion (TI) is a paradigmatic example of contextual influences on perception of central target. The phenomenon shows a characteristic dependence on the angle between the inducing surround stimulus and the central target test. For small angles there is a repulsion effect, for larger angles there is a smaller attraction effect. The center-surround inhibition in tilt repulsion is considered to come from spatial orientational interactions between orientation-tuned neurons in V1, and tilt attraction from higher-level effects of orientation processing in the visual information processing. Objectives The present study focuses on visual spatial information processing and explores whether chronic AUD patients in abstinence period exhibited abnormal TI compared with healthy controls. Methods The participants are 30 male volunteers (20–46 years of old) divided into two groups: the study group consists of 15 clinically diagnosed AUD patients undergoing abstinence from alcohol and the control group consists of 15 healthy volunteers. The TI consists of a center target surround with an annulus (both target and annulus are sinusoidal grating with spatial frequency = 2 cycles per degree). The visual angle between center and surround is a variable restricted to 0°, ±15°, ±30°, or ±75°. For measuring the TI, participants have to report whether the center target grating orientation tilted clockwise (CW) or counterclockwise (CCW) from the internal vertical orientation by pressing corresponding keys on the computer keyboard. No feedback is provided regarding response correctness. Results The results reveals significantly weaker tilt repulsion effect under surround orientation ±15 degree (p < 0.05) and higher lapse rate (attention limitation index) under all tested surround orientations (all ps < 0.05) in patients with chronic AUD compared with health controls. Conclusions These results provide psychophysical evidences that visual perception of center-contextual stimuli is different between AUD and healthy control groups.